2021
DOI: 10.1016/j.heliyon.2021.e08230
|View full text |Cite
|
Sign up to set email alerts
|

A modified theory of planned behavioral: A case of tourist intention to visit a destination post pandemic Covid-19 in Indonesia

Abstract: The Pandemic covid-19 spread globally has been given impact in the tourism industry, especially in the tourism destination. This study investigated to build the concept and theoretical framework that explains the decision of local tourist intention to visit a local destination in Indonesia post-pandemic covid-19. This study was considered the perception of Covid-19, non-pharmaceutical intervention and health consciousness by implying of Theory of Planned Behavior constructs. This study, health consciousness is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 88 publications
(125 reference statements)
7
64
0
4
Order By: Relevance
“…From the results of the study, two variables in the TPB model are Attitude andand PBC (Percieved Behavioral Control) has a positive and significant effect on the intention to travel to Sabang City in the midst of the Covid 19 pandemic, where Attitude is the variable that has the largest contribution in influencing Intention. These empirical findings are in line with the findings of other researchers using the TPB model and in the context the COVID-19 pandemic (Sandra, et al, 2020, Bae & Chang, 2020, Li, et al, 2020, Xu, et al, 2021, Pahrudin, et al, 2021, and Sujood, et al, 2021.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…From the results of the study, two variables in the TPB model are Attitude andand PBC (Percieved Behavioral Control) has a positive and significant effect on the intention to travel to Sabang City in the midst of the Covid 19 pandemic, where Attitude is the variable that has the largest contribution in influencing Intention. These empirical findings are in line with the findings of other researchers using the TPB model and in the context the COVID-19 pandemic (Sandra, et al, 2020, Bae & Chang, 2020, Li, et al, 2020, Xu, et al, 2021, Pahrudin, et al, 2021, and Sujood, et al, 2021.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, the results of this study indicate that the Subjective Norm has no effect on Intentions traveling to Sabang City in the midst of the Covid 19 pandemic, these findings are in accordance with (Pahrudin, et al, 2021, andSujood, et al, 2021) who confirmed that the Subjective Norm was not significant for predicting the intention to travel during the COVID-19 pandemic situation. In contrast, with the model and context of COVID-19, several other researchers found a significant influence on the Subjective Norm.…”
Section: Discussionsupporting
confidence: 82%
“…The hypothesized research model integrated media credibility and risk perception into TPB that was empirically measured using online survey data collected from tourists concerning the impact of media credibility on behavioral intention through risk perception (See Figure 1). In the current study, the questionnaire items employed maturity scales that have been verified in prior studies, such as that of Ajzen [42], Rahmafitria et al [34], Pahrudin [43], to guarantee content validity. Furthermore, certain appropriate revisions were made so as to better gauge the touristic behavior of Chinese residents in the postpandemic context.…”
Section: Measuring Of the Constructsmentioning
confidence: 99%
“…Perceived behavioral control: five items modified from Harmid and Bano [48] and Pahrudin et al [43]. Sample item: I am confident that traveling in the post-pandemic context is entirely within my control.…”
mentioning
confidence: 99%
“…A number of studies to date have extended the TPB to various contexts, including tourism and hospitality. Some examples include leisure activities [28], destination choice [29,30], festival visits [31], tourism information adoption (e.g., [32]), lodging [33], tourists' civilized behaviors [34] and environmental behaviors [24,35]. In the context of service, Shaaban and Maherr [36] have applied the TPB to predict the use of public transportation services.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%